Improvement in Emotion Regulation While Detained Predicts Lower Juvenile Recidivism. (April 2022) - Docherty, Meagan; Lieman, Andrew; Gordon, Brandon Lee
The goal of the current study was to investigate the relationships between observer-rated skills related to emotional and cognitive regulation post-admission and pre-release in a secure facility and official records of juvenile felony recidivism up to 1 year after release. Data came from a sample of 599 youth in a residential facility in Washington state (84% male; 38% White). Latent change score models indicated that both initial level of emotional regulation skills and improvement in emotion regulation skills while incarcerated were significantly related to lower recidivism. This pattern of findings remained when controlling for length of stay, among other covariates. Follow-up analyses indicated that the results for emotion regulation skills might be driven primarily by monitoring internal and external triggers. Additional research should investigate the connection between emotion regulation skills and juvenile recidivism, with a special focus on trigger monitoring and how to improve those skills.